2019
DOI: 10.1101/746255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The translation inhibitor cycloheximide affects ribosome profiling data in a species-specific manner

Abstract: Ribosome profiling provides genome-wide snapshots of translation dynamics by determining ribosomal positions at sub-codon resolution. To maintain this positional information, the translation inhibitor cycloheximide (CHX) has been widely used to arrest translating ribosomes prior to library preparation. Several studies have reported CHX-induced biases in yeast data casting uncertainty about its continued use and questioning the accuracy of many ribosome profiling studies. However, the presence of these biases h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…However, it seems likely that cycloheximide treatment has less of an effect in humans and some other organisms, compared to yeast and fly, not impacting transcript-specific ribosome occupancy ( Sharma et al, 2021 ). Both the results presented here in Drosophila and other studies have shown that cycloheximide treatment does not affect either footprint size distribution or framing ( Sharma et al, 2019 ). Snap freezing material is an alternative to ‘trapping’ ribosomes during elongation using cycloheximde, which does not seem to affect framing, read length or distribution.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, it seems likely that cycloheximide treatment has less of an effect in humans and some other organisms, compared to yeast and fly, not impacting transcript-specific ribosome occupancy ( Sharma et al, 2021 ). Both the results presented here in Drosophila and other studies have shown that cycloheximide treatment does not affect either footprint size distribution or framing ( Sharma et al, 2019 ). Snap freezing material is an alternative to ‘trapping’ ribosomes during elongation using cycloheximde, which does not seem to affect framing, read length or distribution.…”
Section: Discussionsupporting
confidence: 73%
“…Metagene analysis revealed that cycloheximide treatment had a limited effect on footprint length or periodicity with Buffer 1, A-RNaseI (comparing Supplementary Figure S4A and Figure 3A ) and Buffer 2 E-RNAseI (comparing Supplementary Figure S4B and Figure 2B ). The distribution of reads across CDSs is affected by cycloheximide treatment, as previously described in other organisms ( Duncan and Mata, 2017 ; Gerashchenko and Gladyshev, 2014 ; Hussmann et al, 2015 ; Sharma et al, 2019 ). Specifically, cycloheximide treatment results in a build-up of Ribo-Seq reads at the start codon and in the first ∼15 nt of CDSs ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 69%
“…Flash-freezing and rapid thawing followed by disruption in the presence of high concentrations of CHX allowed to minimize artifacts associated with the CHX treatment (56). We note that no CHX-induced artifacts were reported for animal tissue samples (57). After homogenization and centrifugation, 250 μL of lysate were supplied with 20 units of SUPERase-In RNase inhibitor and taken for RNA-seq library preparation, and the 500 μL of lysate was brought to 1 mL with lysis buffer and taken for Ribo-seq library preparation.…”
Section: Methodsmentioning
confidence: 84%
“…Other groups have had success using double-strand specific DNase, combined with a high-temperature re-annealing of the final DNA library that only leaves the most abundant sequences (the rRNA fragments) doublestranded (Chung et al 2015), but this method has not to our knowledge been tested on a broad range of fragment lengths, nor with improved library preparation methods such as randomized unique molecular identifiers (McGlincy and Ingolia 2017). Recent reports indicate that optimization of RNase digestion conditions (Sharma et al 2019) as well as judicious choice of RNase enzyme (Gerashchenko and Gladyshev 2017) can also reduce the rRNA content of ribosome profiling libraries, though many procedures using these different nucleases obscure the high resolution information on ribosome position and A site status. Finally, it is important to note that off-target RNaseH activity will not only affect the conclusions of ribosome footprint profiling experiments, but of any protocol that requires precise knowledge of the 5′ and 3′ ends of RNA fragments.…”
Section: Discussionmentioning
confidence: 99%